TAMAN SEDATI GEDE SEBAGAI AKAR UDARA BERSIH INTERAKSI DAN KENYAMANAN BAGI MASYARAKAT - Rina Fariana; Dian Nurul Sholihatin; Tarisa Dwi Savitri; Dzul Kamalil Qorihah; Muhammad Maulana Alamsyah; Arief Multi Prawira Diharja (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
A location with shady greening is indeed very much needed by every region, one of which is Sedati Gede Village in Sedati Sidoarjo district. The rapid access in this village has a bad impact on the empowerment of existing parks. Therefore, participants of the Real Work Lecture from PGRI Adi Buana University Surabaya carried one of their programs, namely the creation and maintenance of the Sedati Gede green park. This park will later become a place with a source of clean air, comfort, and as an interacting area for the community and other living things. These benefits are also supported by good waste management efforts in the park area by doing 1) reduce, reuse, recycle 2) reduce plastic waste, and 3) reduce food packaging waste. With these efforts, maintenance, and regular maintenance, Sedati Gede park is ready to become a green acre that has a positive impact on the community and others